Asymmetric Intermixing and the Stress Buildup in Ni/Al-typed Nanomultilayer with Different Characteristic Scales. Issue 11 (November 2017) - Mingxia, Liu; Fei, Ma; Gengrong, Chang; Binfeng, He; Fuxing, Fu; Fangxia, Ye; Lijun, Yu; Jun, Dai; Kewei, Xu
Abstract: In order to detect scale-dependent interfacial evolution of metallic heterostructure during the deposition at room temperature, Ni/Al-typed nanomultilayers were prepared as a function of the periodicity and Ni:Al modulated ratio. Combined with X-ray diffraction, real-time plate curvature measurements by multi-beam optical stress sensor (MOSS) were employed to study the stress buildup so as to speculate interfacial characteristics during the growth process. Results show that with anisotropic nanocrystalline structure within the sub-layers, the multilayers possess asymmetrical interfaces, which is a result of dissymmetrical diffusion of Ni to Al lattice near the interface. Specially, for the smallest periodicity with the lowest Ni:Al ratio, above asymmetric intermixing behaviors turns to be aggravated by a promotion effect.